MANAJEMEN PENINGKATAN MUTU SARANA DAN PRASARANA PENDIDIKAN DI UPTD SDN 232 TELLESANG KECAMATAN PITUMPANUA - Hasni; H. Darmawan; Sumarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the management of quality improvement in educational facilities and infrastructure at UPTD SDN 232 Tellesang in Pitumpanua District. The study employs a descriptive qualitative approach using purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using an interactive model involving data reduction, data presentation, and the drawing of conclusions and verification. The results of the study indicate that the management of facilities and infrastructure has been carried out systematically through the identification of needs, clear division of tasks, procurement and utilization of educational facilities, as well as regular monitoring and evaluation. This management has a positive impact on the effectiveness of learning and the improvement of educational quality. Supporting factors include the leadership of the school principal, cooperation among school community members, and support from the committee and the community, while inhibiting factors include budget constraints, technological needs, and facility maintenance costs.